What Is the Share of the Country's Researches in Iran's National Tuberculosis Guideline? - Reza Majdzadeh; Khaled Rahmani; Mahshid Nasehi (Tehran University of Medical Sciences, 2013)
Appraisal of clinical guideline, especially at the national level, has two potential benefits; one is the improvement of quality of care and the second is assessing the impact of researches on an applied setting. On the other hand, Tuberculosis (TB) is a major infectious disease which has national guideline in many countries. The present study was performed to assess sources of information and level of evidence in Iran's national TB guideline. This could explore the impact of national researches on day by day practice in the health system.A list of main "recommendations" of the guideline was explored. Then, in cases that the cited study for any decision was available, the type of study and its evidence level was specified using a standard tool. In addition, the source of information (national/international) was determined. In other cases that no any specific citation was found, the data source of the recommendation was determined by the senior experts in the Center for Communicable Disease Control.Fifteen (48.3%) recommendations of the national guideline, out of 31 reviewed, had clearly cited at least one study. There was just one single national study which was utilized as the basis for the recommendations. All other sources were international guidelines, mainly World Health Organization's, and or international researches.While, the methodology of the guideline development was not clear enough appropriately; the share of national researches in development of the national guideline was insignificant.